Poor Poverty The Impoverishment of Analysis, Measurement and Policies - Sundaram, Jomo Kwame; Chowdhury, Anisuzzaman (The United Nations Series on Development, 2011)
This book, co-published with the UN's Dept of Economic and Social Affairs, offers a critical appraisal of the conventional measures and analysis of poverty as well as of poverty reduction policies. It is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. Despite greater efforts in reducing poverty since the early 1980s, poverty remains stubbornly high in many parts of the world. This collection argues that the mainstream perspectives on poverty and deprivation have contributed to considerable distortion and misunderstanding and that is not unrelated to ineffectual policy perscriptions. In particular it highlights the World Bank's dollar-a-day measure of poverty and exposes the inadequacies of Bretton Woods-inspired poverty reduction programmes.